A comparison of tramadol with morphine for intravenous patient controlled analgesia [Intravenoz hasta kontrollu analjezi yonteminde tramadolun morfin ile karsilastirilmasi] - (:unkn) unknown (My University, 2000)
The aim of this study was to compare tramadol with morphine for IV PCA following total abdominal hysterectomy. After a standardized general anaesthesia, in the recovery room; 22 female patients aged between 20-60 years were randomly assigned into two groups. In group I; patients received an initial of 4 mg morphine followed by 1 mg every 5 min and in group II; they received an initial of 100 mg tramadol followed by 20 mg every 5 min as loading doses. The demand dose of PCA was 1.5 mg morphine and 20 mg tramadol with a 10 min lockout period. The mean 48 h consumption of morphine and tramadol were 58.45±32.57 mg and 734.54±154.1 mg respectively. The estimated relative potency of tramadol to morphine was 12.6:1. The pain scores of group I decreased at 2nd hour while it was significant at 4th hour in group II. Also the pain scores of group I were significantly lower than those of group II at 1st and 2nd hour (p<0.001). The mostly seen side effect was nausea occuring in 9 of 11 (81%) patients in each group. We concluded that for postoperative IV PCA; morphine is superior to tramadol as it provided effective analgesia earlier while the incidence of side effects did not differ.
Keywords: Morphine; Patient-controlled analgesia; Tramadol